2019
DOI: 10.5194/acp-19-1-2019
|View full text |Cite
|
Sign up to set email alerts
|

The significant contribution of HONO to secondary pollutants during a severe winter pollution event in southern China

Abstract: Abstract. Nitrous acid (HONO) can strongly affect atmospheric photochemistry in polluted regions through the production of hydroxyl radicals (OHs). In January 2017, a severe pollution episode occurred in the Pearl River Delta (PRD) of China, with maximum hourly PM2.5, ozone, and HONO levels reaching 400 µg m−3, 150 ppb, and 8 ppb, respectively, at a suburban site. The present study investigated the sources and processes generating such high HONO concentrations and the role of HONO chemistry in this severe wint… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(118 citation statements)
references
References 76 publications
9
90
1
Order By: Relevance
“…2 and 3) was fitted as a linear function of [H 2 O], as (3.0 ± 0.4) × 10 4 × [H 2 O]. This value is in reasonable agreement with the values of (2.7-3.8) ×10 4 , ∼ 3.9 × 10 4 , and 2.6 × 10 4 M −1 s −1 determined from ammonium bisulfate, ammonium sulfate (Gaston and Thornton, 2016), and aqueous organic acid particles (Thornton et al, 2003), respectively. Compared to original BT09 (Eq.…”
Section: Observation-based Empirical Parameterization Of γ N 2 Osupporting
confidence: 81%
See 1 more Smart Citation
“…2 and 3) was fitted as a linear function of [H 2 O], as (3.0 ± 0.4) × 10 4 × [H 2 O]. This value is in reasonable agreement with the values of (2.7-3.8) ×10 4 , ∼ 3.9 × 10 4 , and 2.6 × 10 4 M −1 s −1 determined from ammonium bisulfate, ammonium sulfate (Gaston and Thornton, 2016), and aqueous organic acid particles (Thornton et al, 2003), respectively. Compared to original BT09 (Eq.…”
Section: Observation-based Empirical Parameterization Of γ N 2 Osupporting
confidence: 81%
“…S2). Different dimensionless K H values have been used in previous studies, e.g., ∼ 50 (e.g., Hallquist et al, 2003;Bertram and Thornton, 2009) or ∼ 120 (e.g., Gaston et al, 2014;Gaston and Thornton, 2016;Griffiths et al, 2009), which correspond to a Henry's law constant of 2 or 5 M atm −1 at 298 K. As γ N 2 O 5 in the parameterization is linearly dependent on the K H , an increase of K H value would proportionally increase the γ N 2 O 5 value, but it cannot account for the large variability of measured γ N 2 O 5 values. Given the lack of an explicit function of effective Henry's law constant for N 2 O 5 to include the different processes (e.g., "salting-in" effect and surface processes), we use the value of 51 suggested by Bertram and Thornton (2009) and enclose those effects from the aerosol composition in the last "chemical" term.…”
Section: Observation-based Empirical Parameterization Of γ N 2 Omentioning
confidence: 99%
“…Several potential factors were found to be responsible for the model deviation and differences, including the emission inventories, chemistry-meteorology coupling effects, bidirectional exchange of NH 3 and the NH 3 gas-aerosol partitioning, which are all important aspects with respect to the model improvements in future. Previous studies also suggest that the nitrous acid (HONO) chemistry plays an important role in the atmospheric nitrogen chemistry, which influences the simulations of NO 2 and NH 3 (Fu et al, 2019;Zhang et al, 2017Zhang et al, , 2016. Heterogeneous conversion from NO 2 to HONO (2NO 2(g) + H 2 O (l) → HONO (l) + HNO 3(l) ) is one of the dominant sources of HONO in the atmosphere, which has been considered in most models of MICS-Asia III, including CMAQ since version 4.7, NAQPMS, NHM-Chem and GEOS-Chem.…”
Section: Discussionmentioning
confidence: 99%
“…However, this method is more suited to deal with the uncertainty related to the continuous variables, such as input data or parameters in parameterization. The ensemble method, based on a set of different models, is an alternative approach to accounting for the range of uncertainties (Galmarini et al, 2004;Mallet and Sportisse, 2006). For example, the Air Quality Model Evaluation International Initiative (AQMEII) has been implemented in Europe and North America to investigate the model uncertainties of their regional-scale model predictions (Rao et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Differences of the zonal mean zonal wind in the extratropics, around ±10 %, are not significant and are mainly caused by a meridional shift of the higher-latitude wind systems. Punge et al (2009) showed that meridional transport in the tropics and subtropics depends on the QBO phase. Figure 2 shows that both eruption phases inject into easterly zonal wind.…”
Section: Transport Of Aerosolsmentioning
confidence: 99%